PENGARUH MODAL KERJA DAN PERPUTARAN PIUTANG TERHADAP LABA BERSIH - Kholifah, Fasha Nur; Oktavianna, Rakhmawati (Publika Citra Media, 2024)
This research aims to determine the effect of working capital and accounts receivable turnover on net profit. The type of research used in this research is quantitative. The data source used is secondary data, namely annual financial reports obtained from the Indonesia Stock Exchange (BEI). The population used in this research is healthcare companies listed on the IDX in the 2018-2022 period. The sample selection technique used purposive sampling and 12 companies were obtained over a 5 year period with a total of 60 sample data obtained. The results of this research show that the Working Capital variable (X1) partially has a significant effect on Net Profit (Y), and partially that the Receivables Turnover variable (X2) does not have a significant effect on Net Profit (Y).